An unusual presentation of fucosidosis in a Chinese boy: a case report and literature review (childhood fucosidosis) - Shao-Jia Mao; Jia Zhao; Zheng Shen; Chao-Chun Zou (BMC, 2022)
Abstract Background Fucosidosis is one of the rare autosomal recessive lysosomal storage diseases (LSDs) attributed to FUCA1 variants causing the deficiency of α-L-fucosidase in vivo. Α-L-fucosidase deficiency will cause excessive accumulation of fucosylated glycoproteins and glycolipids, which eventually leads to dysfunction in all tissue systems and presents with multiple symptoms. Fucosidosis is a rare disease which is approximately 120 cases have been reported worldwide (Wang, L. et al., J Int Med Res 48, 1-6, 2020). The number of reported cases in China is no more than 10 (Zhang, X. et al., J Int Med Res 49:3000605211005975, 2021). Case presentation The patient was an 8-year-old Chinese boy who presented with postnatal motor retardation, intellectual disability, short stature, language development retardation, coarse facial features, hepatomegaly, and diffuse angiokeratoma of both palms. His genetic testing showed the presence of a homozygous pathogenic variant (c.671delC) in the FUCA1 gene. In addition, the enzymatic activity of α-L-fucosidase was low. Ultimately, the patient was diagnosed with fucosidosis. Conclusions Fucosidosis is a rare lysosomal storage disease because of FUCA1 variants that cause the deficiency of α-L-fucosidase in vivo. An explicit diagnosis requires a combination of clinical manifestations, imaging examination, genetic testing and enzyme activity analysis. Early diagnosis plays an important role in fucosidosis.